2015
DOI: 10.1523/jneurosci.1687-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Saccade Planning Evokes Topographically Specific Activity in the Dorsal and Ventral Streams

Abstract: Saccade planning may invoke spatially-specific feedback signals that bias early visual activity in favor of top-down goals. We tested this hypothesis by measuring cortical activity at the early stages of the dorsal and ventral visual processing streams. Human subjects maintained saccade plans to (prosaccade) or away (antisaccade) from a spatial location over long memory-delays. Results show that cortical activity persists in early visual cortex at the retinotopic location of upcoming saccade goals. Topographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 68 publications
10
42
1
Order By: Relevance
“…Response amplitudes did not significantly differ between covert and overt shift conditions. Therefore, the suggestion that saccade planning can enhance brain activity related to visual processing (Saber et al, 2015) was not confirmed in this study. Enhancement due to planning a saccade may not be significantly different from that due to planning a lateralized manual response.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Response amplitudes did not significantly differ between covert and overt shift conditions. Therefore, the suggestion that saccade planning can enhance brain activity related to visual processing (Saber et al, 2015) was not confirmed in this study. Enhancement due to planning a saccade may not be significantly different from that due to planning a lateralized manual response.…”
Section: Discussioncontrasting
confidence: 70%
“…Functional MRI has been used to investigate covert and overt attention shifts (e.g., Corbetta et al, 1998; Kelley et al, 2008), but its low temporal resolution does not allow eye movements artifacts to be excluded unless subjects are instructed to delay their eye movements (memory guided saccades, e.g., Saber et al, 2015). The temporal resolution of EEG allows selection of data from the period before saccade onset (here up to 180 ms from target onset).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-reach and anti-saccade tasks have been performed to distinguish between sensory target representations and movement plans. During the delay phase preceding a pro-or anti-saccade, the PPC shows a sustained response to both the visual target and the saccade goal, with a stronger response to the visual stimulus during the first part of the delay, and a stronger response to the saccade goal during the second part of the delay (Medendorp et al, 2005;Saber et al, 2015;Van Der Werf et al, 2008). In contrast, participants who were adapted to left-right reversing prisms in a delayed reaching task showed directional selectivity in the PPC that was fixed to the visual coordinates of the remembered goal throughout the delay (Fernandez-ruiz et al, 2007).…”
Section: Saccade-and Illusion-related Activationmentioning
confidence: 99%
“…More recent human neuroimaging studies have used multivariate analyses to successfully decode simple visual features or spatial positions held in WM from delay-period multivoxel activation patterns in regions of posterior occipital and parietal cortex (see Serences et al, 2009; Harrison and Tong, 2009; Ester et al, 2009; Riggall and Postle, 2012; Emrich et al, 2013; Christophel et al, 2012, 2015; Jerde et al, 2012; Saber et al, 2015). Importantly, sustained activity changes can be dissociated from information storage during WM, as decoding is often successful even though the amplitude of the blood-oxygenation-level-dependent (BOLD) response typically returns to baseline levels during the memory delay period (Serences et al, 2009; Harrison and Tong, 2009; Riggall and Postle, 2012; Emrich et al, 2013).…”
Section: Introductionmentioning
confidence: 99%